1997
DOI: 10.1139/y97-158
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol metabolism in SM-3 smooth muscle cells

Abstract: The metabolism of endogenous and exogenous diacylglycerol (DG) was studied in SM-3 cells derived from rabbit aortic smooth muscle to determine the biochemical step(s) responsible for degrading DG second messengers. Incubation of growth-arrested SM-3 cells with [3H]myristate for 2 h resulted in selective labelling of cellular phosphatidylcholine (PC). Addition of bacterial PC-specific phospholipase C (PC-PLC, 20 U) to [3H]myristate-labelled SM-3 cells resulted in a 7.4-fold increase in endogenous radiolabelled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…5b). A similar fate has been reported for a variety of other DG molecular species when added to cells, including those with a fatty acid composition identical to that generated by phosphoinositide hydrolysis (Migas et al, 1997). Thus we conclude that the DG produced as a result of hormonal stimulation is channeled to the DG kinase, as previously suggested (Redman et al, 1995).…”
Section: Discussionsupporting
confidence: 70%
“…5b). A similar fate has been reported for a variety of other DG molecular species when added to cells, including those with a fatty acid composition identical to that generated by phosphoinositide hydrolysis (Migas et al, 1997). Thus we conclude that the DG produced as a result of hormonal stimulation is channeled to the DG kinase, as previously suggested (Redman et al, 1995).…”
Section: Discussionsupporting
confidence: 70%
“…26 -28,50 It was recently demonstrated that bacterial phospholipase C, an enzyme competing with LPL for binding to VSMCs, activates PKC in VSMCs. 51 Our data showing that LPL induces PKC activation in VSMCs and that heat inactivation and PMSF inactivation of the enzyme or heparinase treatment of VSMCs inhibit LPL-induced PKC activation clearly suggest that the enzyme may promote the growth of these cells by stimulating this signaling pathway. The involvement of PKC activation in the direct stimulation of VSMC proliferation by LPL is strengthened by our observations that pharmacological inhibition of PKC by specific PKC inhibitors, including calphostin C and chelerythrin, completely suppresses LPL-induced VSMC proliferation.…”
Section: Discussionmentioning
confidence: 64%
“…Igal et al stated the possible encryption of intracellular DAGs produced in CHO cell plasma membranes after ingestion by phospholipase C in initiating TAG biosynthesis. Meanwhile, the mechanism of DAG lipase inhibitors added via liposome fusion or via soluble dioctanoyl glycerol remain unclear, particularly on their total inhibitory levels to phospholipase C in NIH 3T3 Swiss fibroblasts. These results make certain assumptions on the presence of different molecular routes and releasing domains for phospholipase C and perhaps due to metamorphic crystallization happen under different pH conditions and ion strengths. These statements have logical opinions when we are taking into account the molecular labeling of intermediated enzymes and their targeted substrates.…”
Section: Bioavailability Of Glycerols and Glycerolipidsmentioning
confidence: 99%